Physical Feasibility Study of Agroforestry Farm Systems to Support Sustainable Agriculture in Konaweha Sub Watershed of Southeast Sulawesi - Sitti Marwah (UNIVERSITY OF LAMPUNG, 2012)
The farming systems in Konaweha watershed are mostly mixed garden that are partly managed intensively as wellas traditionally. The objectives of this research were to identify and classify agroforestry systems that were practicedby farmers, to study the effect of the agroforestry systems on soil properties, hydrological indicators, and erosion,as well as to analyze farm management feasibility of agroforestry systems to establish sustainable agriculturesystem. The study was carried out in Konaweha watershed, Southeast Sulawesi. The results indicated thatagroforestry systems in this area were devided into four types i.e. sylvopastoral-perennial crops with pasture,agrosylvicultural-perennial crops, agrosylvicultural-multystrata systems, and sylvopastoral-multystrata systems.The four types of agroforestry systems significantly increased the soil aggregate stability, soil porosity at 30 cm indepth, organic matter, soil organic carbon, and microorganisms population. In addition, the agroforestry haddecreased runoff and erosion significantly. Therefore, the erosion rate from the four types of agroforestry systemwas below the value of tolerated soil loss (TSL), except that of agrosylvicultural-perennial crops with an elevationof > 30%. The best quality of soil and environment was found at sylvopastoral-multystrata systems.Keywords: Agroforestry; erosion; soil properties; sustainable agriculture[How to Cite: Marwah S. 2012. Physical Feasibility Study of Agroforestry Farm Systems to Support Sustainable Agriculture in Konaweha Sub Watershed of Southeast Sulawesi. J Trop Soils, 17 (3) : 275-282. doi: 10.5400/jts.2012.17.3.275][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.275]